Elementary Accounting: Theory, Technique, and Applications (Book). - Sterling, Robert R.; Tidyman, Clayton R. (The Accounting Review, 1970)
Reviews the book "Elementary Accounting: Theory, Technique, and Applications," by Robert E. Seiler.